UPAYA MENGENALI KETERAMPILAN MEMBACA PEMAHAMAN MELALUI ASESMEN BAGI ANAK BERKESULITAN BELAJAR MEMBACA DI KELAS 3 SD NEGERI 12 SRAGEN - Rosita, Yosy (Pendidikan Luar Biasa, 2013)
This research aims to: a) find out the reading skill level of the third graders of SD N 12 Sragen, b) find out the extent to which the assessment contributes to identifying the children with reading comprehension difficulty, c) find out the number of students with reading comprehension learning difficulty, d)  predict the factors causing the students have reading comprehension difficulty, and e) predict the appropriate learning follow-up to give to the children with reading comprehension difficulty. This study employed a qualitative research method. The subject of research was the third graders of SD Negeri 12 Sragen consisting of 50 students. The sampling technique used was total sampling technique, the one in which the number of samples equals to that of population. Technique of collecting data used was data triangulation (observation, interview, and document). The data analysis was carried out using interactive and flowing analyses. The result of research showed that having conducted assessment, it could be found that in fact the student ability of answering and comprehending the content of reading was still low, the assessment played an important role in identifying the children with reading comprehension disability. Thirteen out of 50 students were learning disabled. The factors causing the students had learning disability included family (7%), economic (15%), physical (7%), low IQ (15%), lazy (30%), and multiple symptoms (23%). Then, the follow-up used was to make academic remedy or Individualized Teaching Program (PPI). Considering the result of research, it could be concluded that the assessment of learning difficulty was important to identify the reading comprehension skill of the third graders of regular Elementary School in Sragen Subdistrict, Sragen Regency, in the school year of 2011/2012, so that the learning program could be determined later. Keywords: assessment, learning difficulty, reading comprehension.